The effect of proteolytic enzyme serratiopeptidase in the treatment of experimental implant-related infection - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2006)
Background: Infection around an implanted orthopaedic device is a devastating complication, and the treatment of infections involving slime-forming bacteria is especially difficult. The purpose of the present study was to evaluate the effectiveness of a proteolytic enzyme, serratiopeptidase, in the eradication of a periprosthetic infection in an in vivo animal model. Methods: In sixty Sprague-Dawley rats, the medullary canal of the right femur was drilled through the intercondylar notch and was inoculated with a Staphylococcus epidermidis strain (ATCC 35984) with a high slime-producing capacity. The cavity was filled with polymethylmethacrylate cement, and a Kirschner wire that had contact with the knee joint was inserted. None of the animals received any treatment for two weeks. Twenty rats were killed at two weeks after the inoculation in order to determine if the infection had become established. The remaining forty rats were randomized into two groups. One group received serratiopeptidase enzyme injections into the knee joint in addition to antibiotic therapy for four weeks, and the other group received intra-articular saline solution injections together with the same antibiotic therapy. The animals from both groups were killed two weeks after the end of therapy (on Day 56). The knee specimens were evaluated bacteriologically and histologically to determine the prevalence of persistent infection and the effects of the enzyme on local tissue. Results: At two weeks, inoculated bacteria grew on culture of specimens from twelve (63.2%) of nineteen animals in the no-treatment group. Microbiological testing suggested that infection persisted in only one (5.6%) of eighteen animals in the serratiopeptidase-and-antibiotic group, whereas it was present in six (37.5%) of sixteen animals in the antibiotic-only group (p = 0.001). Histological evaluation showed similar results (kappa = 0.92). Conclusions: Serratiopeptidase was effective for eradicating infection caused by biofilm-forming bacteria in this experimental animal model. The antibiofilm property of the enzyme may enhance antibiotic efficacy in the treatment of staphylococcal infections.
Keywords: TOTAL KNEE ARTHROPLASTY; TOTAL JOINT REPLACEMENT; 2-STAGE REIMPLANTATION; DOUBLE-BLIND; CANINE MODEL; OSTEOMYELITIS; UROKINASE; ADHERENCE; SALVAGE; PLACEBO